Transformer Core And Winding Conditions Evaluation From Sfra Measurement Results Using Cross-Correlation Coefficient Function For Tnb Distribution Transformers - Ab Ghani, Sharin; Thayoob, Y.H.M; Ghazali, Y.Z.Y; Ahmad Khiar, Mohd Shahril; Sutan Chairul, Imran (2012)
Distribution transformers in TNB (Tenaga Nasional Berhad) Malaysia arc exposed to the thermal and electrical stresses. Those stresses are effecting to the main mechanical active parts in transformer such as core and winding. In field, lightning strikes and cable faults may cause problem due to transformer core and winding. SFRA diagnosis is made based on the comparison between two SFRA responses md any significant difference in low, middle and high frequency sub-bands region would potentially indicate mechanical or electrical problem due to core and winding of transformer. instead of using graphical comparison, numerical technique such as Cross-correlation Coefficient Function (CCF) can be used to interpret the SFRA results in n proper say. The aim of this paper is to assess the condition of TNB distribution transformer by using SFRA method in line with the interpretation from the CCF technique.